Impact of atrial fibrillation on outcome in takotsubo syndrome: data from the International Takotsubo Registry - El-Battrawy, Ibrahim; Cammann, Victoria Lucia; Kato, Ken; Szawan, Konrad Andreas; Di Vece, Davide; Rossi, Aurelio; Wischnewsky, Manfred; Hermes‐Laufer, Julia; Gili, Sebastiano; Citro, Rodolfo; Bossone, Eduardo; Neuhaus, Michael; et al. (Journal of the American Heart Association, 2021)
Background - - Atrial fibrillation (AF) is a major risk factor for mortality. The prevalence, clinical correlates, and prognostic impact of AF in Takotsubo syndrome (TTS) have not yet been investigated in a large patient cohort. This study aimed to investigate the prevalence, clinical correlates, and prognostic impact of AF in patients with TTS. - - Methods and Results - - Patients with TTS were enrolled from the International Takotsubo Registry, which is a multinational network with 26 participating centers in Europe and the United States. Patients were dichotomized according to the presence or absence of AF at the time of admission. Of 1584 patients with TTS, 112 (7.1%) had AF. The mean age was higher (P<0.001), and there were fewer women (P=0.046) in the AF than in the non‐AF group. Left ventricular ejection fraction was significantly lower (P=0.001), and cardiogenic shock was more often observed (P<0.001) in the AF group. Both in‐hospital (P<0.001) and long‐term mortality (P<0.001) were higher in the AF group. Multivariable Cox regression analysis revealed that AF was independently associated with higher long‐term mortality (hazard ratio, 2.31; 95% CI, 1.50-3.55; P<0.001). Among patients with AF on admission, 42% had no known history of AF before the acute TTS event, and such patients had comparable in‐hospital and long‐term outcomes compared with those with a history of AF. - - Conclusions - - In patients presenting with TTS, AF on admission is significantly associated with increased in‐hospital and long‐term mortality rates. Whether antiarrhythmics and/or cardioversion are beneficial in TTS with AF should thus be tested in a future trial. - - Registration - - URL: https://www.clinicaltrials.gov; Unique identifier: NCT01947621.